2023
DOI: 10.1093/molbev/msad099
|View full text |Cite
|
Sign up to set email alerts
|

Principles of Cold Adaptation of Fish Lactate Dehydrogenases Revealed by Computer Simulations of the Catalytic Reaction

Abstract: Cold-adapted enzymes from psychrophilic and psychrotolerant species are characterized by a higher catalytic activity at low temperature than their mesophilic orthologs and are also usually found to be more thermolabile. Computer simulations of the catalytic reactions have been shown to be a very powerful tool for analyzing the structural and energetic origins of these effects. Here, we examine the cold-adaptation of lactate dehydrogenases from two Antarctic and sub-Antarctic fish species using this approach an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 42 publications
1
8
0
Order By: Relevance
“…Hence, all of the loops covering the active site are fully mobile and it is, in fact, only 163 atoms (belonging to 16 residues) on the back side of the enzyme that are restrained. This type of simulation model has been shown earlier for numerous systems to give accurate values of thermodynamic activation parameters compared to experiment. In particular, the model has also been shown to capture the curved Arrhenius plot for a cold-adapted α-amylase, demonstrating that the curvature is not due to a heat capacity effect but to the existence of an inactive state of the ES complex . This has recently also been verified by us experimentally by redesign of the α-amylase .…”
supporting
confidence: 60%
“…Hence, all of the loops covering the active site are fully mobile and it is, in fact, only 163 atoms (belonging to 16 residues) on the back side of the enzyme that are restrained. This type of simulation model has been shown earlier for numerous systems to give accurate values of thermodynamic activation parameters compared to experiment. In particular, the model has also been shown to capture the curved Arrhenius plot for a cold-adapted α-amylase, demonstrating that the curvature is not due to a heat capacity effect but to the existence of an inactive state of the ES complex . This has recently also been verified by us experimentally by redesign of the α-amylase .…”
supporting
confidence: 60%
“…LDH is the most widely researched enzyme in fish. It is a cytosolic enzyme that catalyses the interconversion of lactate to pyruvate in the final step of anaerobic glycolysis and also the conversion of lactate to glucose during gluconeogenesis (Zakhartsev et al 2004;Koenekoop and Åqvist 2023). It is a tetrameric protein that is controlled by three distinct genes viz., LDH-A*, LDH-B*, and LDH-C*.…”
Section: Heart 4 Discussionmentioning
confidence: 99%
“…Among the examples given above, we have representatives of all four variants of EVB parametrization (solution experiments, 10 solution DFT, 3,4,7 enzyme cluster DFT, 9 and enzyme QM/MM DFT) 5,6 and the predicted values of ΔH ⧧ and ΔS ⧧ are in all cases remarkably good.…”
Section: ■ Introductionmentioning
confidence: 97%
“…For a number of examined enzyme reactions, we found that the calculated thermodynamic activation parameters are in remarkably good agreement with experimental measurements. Some recent examples of this are cytidine deaminase, 9 EF-Tu catalyzed GTP hydrolysis on the ribosome, 10 α-amylase, 4 hydroxybutyrate dehydrogenase, 5 lactate dehydrogenase, 6 and chorismate mutase. 7 The most recent case of chorismate mutase is particularly instructive, since it is a unimolecular reaction in the enzyme (and in solution), with no enzymic groups participating in the actual chemistry.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation